Epidemiological and clinical characteristics of death from hemorrhagic fever with renal syndrome: a meta-analysis - Lu, Wei; Kuang, Lin; Hu, Yuxing; Shi, Jialing; Li, Qi; Tian, Wen (Frontiers in Microbiology, 2024)
Hemorrhagic fever with renal syndrome (HFRS) is an acute infectious disease comprising five stages: fever, hypotension, oliguria, diuresis (polyuria), and convalescence. Increased vascular permeability, coagulopathy, and renal injury are typical clinical features of HFRS, which has a case fatality rate of 1%-15%. Despite this, a comprehensive metaanalyses of the clinical characteristics of patients who died from HFRS is lacking.Methods: Eleven Chinese-and English-language research databases were searched, including the China National Knowledge Infrastructure Database, Wanfang Database, SinoMed, VIP Database, PubMed, Embase, Scopus, Cochrane Library, Web of Science, Proquest, and Ovid, up to October 5, 2023. The search focused on clinical features of patients who died from HFRS. The extracted data were analyzed using STATA 14.0.Results: A total of 37 articles on 140,295 patients with laboratory-confirmed HFRS were included. Categorizing patients into those who died and those who survived, it was found that patients who died were older and more likely to smoke, have hypertension, and have diabetes. Significant differences were also observed in the clinical manifestations of multiple organ dysfunction syndrome, shock, occurrence of overlapping disease courses, cerebral edema, cerebral hemorrhage, toxic encephalopathy, convulsions, arrhythmias, heart failure, dyspnea, acute respiratory distress syndrome, pulmonary infection, liver damage, gastrointestinal bleeding, acute kidney injury, and urine protein levels. Compared to patients who survived, those who died were more likely to demonstrate elevated leukocyte count; decreased platelet count; increased lactate dehydrogenase, alanine aminotransferase, and aspartate aminotransferase levels; prolonged activated partial thromboplastin time and prothrombin time; and low albumin and chloride levels and were more likely to use continuous renal therapy. Interestingly, patients who died received less dialysis and had shorter average length of hospital stay than those who survived.Older patients and those with histories of smoking, hypertension, diabetes, central nervous system damage, heart damage, liver damage, kidney damage, or multiorgan dysfunction were at a high risk of death. The results can be used to assess patients' clinical presentations and assist with prognostication.